Study on preparation of CNTs-Cu composites materials by hydrazine hydrate reduction-solid state sintering process. (10th December 2017) - Yulong, Li; Zaiyuan, Li; Yifei, Luo; Bohui, Li
ABSTRACT: In this paper, the 8% CNTs-Cu and 16% CNTs-Cu composite powders were synthesized by chemical co-precipitation method, in which hydrazine hydrate was used as reductant. The parameters of precipitation process are chosen as follows: co-precipitation temperature was set as 70°C, stirring rate was set to be 600 rpm, pH was designed as 10, dripping reaction time was 120 min and the drying temperature was 50°C. Carbon nanotubes (CNTs), Copper sulfate, sodium hydroxide and hydrazine hydrate were used as raw materials. 8% CNTs-Cu composite bulks were prepared by a solid-phase sintering process under the condition that molding temperature was 800°C, while 16% CNTs-Cu composite bulks cannot be prepared by the same method.